Implementasi Metode Random Forest Untuk Penjurusan Siswa Di Madrasah Aliyah Negeri Sintang - Fajar Mu'alim; Rahmi Hidayati (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
MAN Sintang is the top Islamic superior school in West Kalimantan's Sintang Regency. Science, Social Sciences, and Religion are the three majors of MAN Sintang. According to the 2013 curriculum, majors are conducted at MAN Sintang for students in class X (ten). The difficulty in determining majors for MAN Sintang students is that it takes a long time and is less accurate to find majors that match the student's talents. Student majors are conducted by the MAN Sintang using manual methods to calculate student scores. MAN Sintang can now do student majors using a classification system thanks to technological advancements. The Random Forest approach was utilized to classify the majors of the students in this study. This method is used to determine the final outcomes of the classification of student majors based on voting results. The findings of employing 210 training data and 90 test data to assess the application of student majors classification at MAN Sintang yielded a test accuracy value of 94.38 %.